Overnight staffing in Canadian neonatal and pediatric intensive care units - Christina Maratta; Christina Maratta; Christina Maratta; Christina Maratta; Christina Maratta; Kristen Hutchison; Jessica Nicoll; Jessica Nicoll; Sean M. Bagshaw; John Granton; Haresh Kirpalani; Henry Thomas Stelfox; et al. (Frontiers Media S.A., 2023)
AimInfants and children who require specialized medical attention are admitted to neonatal and pediatric intensive care units (ICUs) for continuous and closely supervised care. Overnight in-house physician coverage is frequently considered the ideal staffing model. It remains unclear how often this is achieved in both pediatric and neonatal ICUs in Canada. The aim of this study is to describe overnight in-house physician staffing in Canadian pediatric and level-3 neonatal ICUs (NICUs) in the pre-COVID-19 era.MethodsA national cross-sectional survey was conducted in 34 NICUs and 19 pediatric ICUs (PICUs). ICU directors or their delegates completed a 29-question survey describing overnight staffing by resident physicians, fellow physicians, nurse practitioners, and attending physicians. A comparative analysis was conducted between ICUs with and without in-house physicians.ResultsWe obtained responses from all 34 NICUs and 19 PICUs included in this study. A total of 44 ICUs (83%) with in-house overnight physician coverage provided advanced technologies, such as extracorporeal life support, and included all ICUs that catered to patients with cardiac, transplant, or trauma conditions. Residents provided the majority of overnight coverage, followed by the Critical Care Medicine fellows. An attending physician was in-house overnight in eight (15%) out of the 53 ICUs, seven of which were NICUs. Residents participating in rotations in the ICU would often have rotation durations of less than 6 weeks and were often responsible for providing care during shifts lasting 20-24 h.ConclusionMost PICUs and level-3 NICUs in Canada have a dedicated in-house physician overnight. These physicians are mainly residents or fellows, but a notable variation exists in this arrangement. The potential effects on patient outcomes, resident learning, and physician satisfaction remain unclear and warrant further investigation.